2021
DOI: 10.25081/jpc.2021.v49.i2.7257
|View full text |Cite
|
Sign up to set email alerts
|

Variability of exotic ginger (Zingiber officinale Rosc.) accessions for quality parameters

Abstract: Ginger (Zingiber officinale) is one of the important and widely used spices throughout the world in fresh and dried forms. The study on quality characterization and essential oil profiling of 13 ginger genotypes was conducted at ICAR-Indian Institute of Spices Research, Kozhikode, Kerala, during 2019-2020. The genotypes included eight promising exotic accessions (Acc. 393, Acc. 607, Acc. 736, Acc. 833, Acc. 869, Acc. 872, Acc. 873 and Acc. 874), four popular cultivars (Nadan, Himachal, Maran, Rio-de-Janeiro) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, this variation of essential oil content might be due to genetic factors of different genotypes from different places of collection. These findings were also supported by earlier studies [31][32][33].…”
Section: Resultssupporting
confidence: 92%
“…However, this variation of essential oil content might be due to genetic factors of different genotypes from different places of collection. These findings were also supported by earlier studies [31][32][33].…”
Section: Resultssupporting
confidence: 92%
“…Maximum temperature attained decrease with increasing soil depths. Balakrishnan et al [24] reported that, there was increase in temperature in solarized plot by 8 O C at 5 cm depth over non-solarized plot. Benefit cost ratio T 1 Rhizome treatment with Streptocycline @ 0.5 g + COC @ 3.0 g/l of water + soil application with neem cake 3q/ha followed by drenching with bleaching powder (33%) @ 2.0 g/l + Metalaxyl MZ @ 1.0 g/lit for water three time at 20 days intervals + Ginger special spray 45 DAS.…”
Section: Soil Solarization Component In the Integrated Disease Manage...mentioning
confidence: 98%
“…Fifty grams (50 g) of the fine powder of each material were introduced in the Clevenger-type apparatus with 0.5 liter of distilled water [10]. The mixture was put under heating at 100˚C using a hot plate-type IRS France and extracted for 2 hours.…”
Section: Extraction Of Essential Oilsmentioning
confidence: 99%
“…Samples from three localities (Kaniamboua, Danyi Apéyémé, Blitta-Tadjan) showed an essential oil yield higher or equal to 1.5%. Steam distillation of Z. officinale essential oil yields 0.2% to 3.0% according to the origin and the state of the rhizome (fresh or dry) [10] [30] [34] [35]. The density of essential oils ranged from 0.876 (Badou) to 0.897 (Blita-Tadjan) and the refractive index from 1.487 (Dalanda and Danyi Apéyémé) to 1.491 (Blitta-Tadjan).…”
Section: Physico-chemical Parameters Of the Z Officinale And Z Zerumb...mentioning
confidence: 99%
See 1 more Smart Citation